Temporal evolution of soil deformations around monopile foundations subjected to cyclic lateral loading. (1st December 2020) - Li, Jialong; Guan, Dawei; Chiew, Yee-Meng; Zhang, Jisheng; Zhao, Jialin
Abstract: Cyclic lateral loading on a monopile in windfarms has been found to cause bed subsidence and convective motions of sediment particles around its foundations. These soil deformations may affect the bearing capacity of the foundation and safety of the structure. This paper presents a 2-dimensional (2D) experimental study on the temporal evolution of bed subsidence and sediment convective-area around vibrating monopiles. The experiments were carried out in a sandbox with a transparent front wall, through which the temporal development of soil deformations around the vibrating monopile can be observed and recorded by using a high definition web camera. The characteristics of the soil subsidence and convective cells are examined with the recorded images, and the influence of the applied force and cyclic loading frequency on the soil deformation process are discussed. The experimental data show that increasing either the force or loading frequency can increase both the temporal development rates and the final size of the subsided bed and convective cells. Empirical equations for depicting the temporal evolution of the subsidence (depth and width) around monopile foundations are proposed. Highlights: Visualization of the process of soil subsidence and sediment convective motions around vibrating monopile foundations. The influence of applied force and cyclic loading frequency on the soil deformation process around monopile foundations. New empirical equations for predicting the temporal evolution of bed subsidence around vibrating monopile foundations.